PEMIKIRAN HUKUM ISLAM PADA MASA KHULAFAUR RASYIDIN : (Cikal Bakal dan Perkembangannya) - Ummu Awaliah; Indo Santalia (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2022)
This study aims to describe the forerunner of Islamic legal thought during the Khulafaur rasyidin era and to explain the development of Islamic legal thought during the Khulafaurrasydin era. This research is qualitative; the type of research is library research and uses a historical approach. The data collection method used is a literature study. The results showed that; 1) It can be understood that the Ansar were the forerunners of the birth of Islamic legal thought regarding the successor of the Prophet as the leader of the state and religion, this can be seen in the event of the meeting at Saqifah Bani Sa'idah in the discussion of the successor of the Prophet. 2) The development of Islamic legal thought during the Khulafaurrasyidin period can be seen in the achievements of the four periods of government. Starting from the caliph Abu Bakr, 'Umar bin Khattab, 'Uṡmān bin 'Affan, and 'Ali bin Abi Talib.